Space Debris Models and Risk Analysis - Klinkrad, Heiner; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2006)
In Space Debris Models and Risk Analysis the authors will provide the reader with a comprehensive background to understand the various sources of space debris, and to assess associated risks due to the current and future space debris environment. Apart from the non-trackable objects produced by historic on-orbit fragmentation events, several other sources of space debris will be outlined. Models will be described to allow the generation and propagation of the different debris families and permit the assessment of the associated collision risk on representative target orbits for present and future conditions. Using traffic models and possible mitigation practices, the future evolution of the space debris environment will be forecast. For large-size, trackable objects methods will be described for conjunction event predictions and related risk assessments. For hazardous re-entry objects, procedures will be outlined to enable the prediction of re-entry times and likely impact areas, to assess uncertainties in these factors, and to quantify the risk due to ground impact. Models will also be described for meteoroids, which prevail over space debris at small particle sizes.
The Current Space Debris Environment and its Sources -- Modeling of the Current Space Debris Environment -- Modeling of Collision Flux for the Current Space Debris Environment -- Modeling of the Future Space Debris Environment -- Effects of Debris Mitigation Measures on Environment Projections -- Hypervelocity Impact Damage Assessment and Protection Techniques -- Operational Collision Avoidance with Regard to Catalog Objects -- Re-Entry Prediction and On-Ground Risk Estimation -- Modeling of the Terrestrial Meteoroid Environment -- Space Debris Activities in an International Context.
Keywords: Engineering; Space sciences; Statistics; Automotive engineering; Aerospace engineering; Astronautics; Quality control; Reliability; Industrial safety; Engineering; Aerospace Technology and Astronautics; Extraterrestrial Physics, Space Sciences; Automotive Engineering; Quality Control, Reliability, Safety and Risk; Statistics for Engineering, Physics, Computer Science, Chemistry and Earth Sciences; Electronic books